Analysis of energy savings for rewinding and replacement of industrial motor - Hasanuzzaman, M.; Rahim, N.A.; Saidur, Rahman (2010)
This study analyzed and estimated economic viability of introducing high efficiency motors compared to the rewind and standard motor in the industrial sector. Efficiency of a motor is degraded when it is rewound. This analysis identified that it is better to rewind a larger motor compared to a smaller motor. It has been found that a high efficiency motor can save an average 5.5 of energy compared to a standard motor. In addition, payback period has been found to be reasonable when a motor is operated at 50 load. It has been estimated that 67,868 MWh/year energy and 4,343,531 US/year bill can be saved for introducing high efficient motors. The present study found that rewind motors of larger size and high efficiency motors are economically viable.